"We are what our bacteria eat": The role of bacteria in personalizing nutrition therapy in gastrointestinal conditions. Issue 2 (February 2017) - Harvie, Ruth; Walmsley, Russell; Schultz, Michael; ,
Abstract: The theme for the 2016 World Digestive Health Day is "Your Diet and Gut Health". The World Gastroenterology Organization thereby wishes to raise awareness of the relationship between what we eat and gastrointestinal symptoms. World Digestive Health Day (WDHD) is celebrated each year on May 29. This brief review article on behalf of the New Zealand Society of Gastroenterology will highlight recent developments in this highly active area of research with a special emphasis on gastrointestinal disorders.